Proposta de aplicação da teoria das restrições no processo de beneficiamento do arroz - Fogaça, Josias Cristiano (2011)
In recent years companies have faced strong pressure from competition, thus seeking new alternatives for management. Thus this study presents a proposal to apply the process of continuous improvement displayed by the Theory of Constraints. This method of management of the restrictions consists of a set of principles and concepts devised by physicist Eliyahu Goldratt and are divided into three areas: logistics, management constraints and thinking process. In the management of the restrictions there are two types of constraints, the physical and nonphysical both found in an organization. The process of continuous improvement that is inserted into the management of the restrictions consists of five steps, identification of the restriction, restriction of exploitation, subordinating everything else to the constraint, elevate the constraint and the last step that suggests a step back if the constraint is broken , these steps were used in this work to demonstrate the application of the Theory of Constraints in rice processing company to increase its gain. Identification of the lapping and polishing operations and system constraints, being exploited through an action plan consisting of priority improvements in equipment and in maintenance. Subordinated to the whole system against the constraint programming using Drum-Buffer-Rope. Conducted lifting the neck through the exchange of current equipment for equipment with greater capacity and so the constraint has been broken giving rise to the new constraint is she the sort operation. With the application of the process of continuous improvement in theory the company increased its production of 4000 kg/h to 5400 kg/h by applying the investment at the site where the gain would be greater.